Keystone sector methodology:network analysis comparative study - Pedro G. Carvalho (European Regional Science Association (ERSA), 2001)
In this paper, we present some new perspectives on rural regional development strategies. Contradictory goals in macroeconomic policies, such as maximizing growth, efficiency and technological innovation with equity or efficient growth with regional disparities, tend to appear with higher costs to small open economies. A large number of studies are focused on this trade-off, using national and some regional aggregate indicators mostly based on economic flows prices and quantities). However the urbanization process is still concentrated in a few traditionally big cities, which is particularly the case in Portugal. The `keystone sector' methodology we apply here shows that other important flows embedded in small town social networks can provide complementary understanding of such issues. Conclusions about a case study in Portugal, its internal and external relations and the comparison with some US similar studies described in the literature, will highlight and enhance the understanding of this approach to the articulation of development strategies in sparsely populated regions in the E.U.
Keywords: 330